Integrated UAV Trajectory Control and Resource Allocation for UAV-Based Wireless Networks with Co-channel Interference Management - Nguyen, Minh Dat; Le, Long Bao; Girard, Andre (IEEE internet of things journal, 2022)
In this paper, we study the trajectory control, sub-channel assignment, and user association design for unmanned aerial vehicles (UAVs)-based wireless networks. We propose a method to optimize the max-min average rate subject to data demand constraints of ground users (GUs) where spectrum reuse and co-channel interference management are considered. The mathematical model is a mixed integer non-linear optimization problem which we solve by using the alternating optimization approach where we iteratively optimize the user association, sub-channel assignment, and UAV trajectory control until convergence. For the sub-channel assignment sub-problem, we propose an iterative sub-channel assignment (ISA) algorithm to obtain an efficient solution. Moreover, the successive convex approximation (SCA) is used to convexify and solve the non-convex UAV trajectory control sub-problem. Via extensive numerical studies, we illustrate the effectiveness of our proposed design considering different UAV flight periods and number of sub-channels and GUs as compared with a simple heuristic.